2020
DOI: 10.4103/jipo.jipo_23_19
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis Infection in Two Patients Treated with Both Immune Checkpoint Inhibitor and Corticoids

Abstract: The introduction of immune checkpoint inhibitor (ICI) targeting cytotoxic T-lymphocyte-associated antigen-4 and programmed cell death receptor 1 has dramatically improved clinical outcome for cancer patients. Nevertheless, this treatment can be associated with immune-related adverse events (irAEs) which sometimes need management with prolonged immune suppression. In order to analyze the risk of Pneumocystis jiroveci pneumonia (PJP) in this population, all PJP cases at our oncological hospital between 2004 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the present patient, IL-6 and TNF-α, inflammatory cytokines released by M1 macrophages at the development of PCP, were elevated, which is consistent with this speculation. Previous cases of PCP during ICI administration were preceded by a history of cytotoxic chemotherapy and steroid administration ( 16 , 17 ), and there have been no reports of PCP during ICI administration in patients without an obvious history of immunosuppressive treatment, such as our case.…”
Section: Discussionmentioning
confidence: 70%
“…In the present patient, IL-6 and TNF-α, inflammatory cytokines released by M1 macrophages at the development of PCP, were elevated, which is consistent with this speculation. Previous cases of PCP during ICI administration were preceded by a history of cytotoxic chemotherapy and steroid administration ( 16 , 17 ), and there have been no reports of PCP during ICI administration in patients without an obvious history of immunosuppressive treatment, such as our case.…”
Section: Discussionmentioning
confidence: 70%
“…Firstly, our post-marketing pharmacovigilance analysis showed that PJP was significantly associated with ICIs. Previous case reports (Arriola et al, 2015;Finbar Slevin et al, 2016;Schwarz et al, 2019;Liu et al, 2020;Moujaess et al, 2020;Sadek et al, 2020;Feng et al, 2021;Rath et al, 2021;Si et al, 2021;Hiba et al, 2022) showed that PJP may be a complication in immunotherapy. But the sample size is small.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO) recommended that primary prophylaxis of Pneumocystis jirovecii pneumonia in patients with hematologic malignancies and solid tumors are warranted ( Classen et al, 2021 ). To the best of our knowledge, only a few case reports/series have described Pneumocystis jirovecii pneumonia (PJP) during pembrolizumab ( Liu et al, 2020 ; Sadek et al, 2020 ; Rath et al, 2021 ; Si et al, 2021 ; Hiba et al, 2022 ; Sanka and Hsu, 2023 ), nivolumab ( Schwarz et al, 2019 ), ipilimumab ( Arriola et al, 2015 ; Finbar Slevin et al, 2016 ; Sadek et al, 2020 ), nivolumab plus ipilimumab ( Moujaess et al, 2020 ) and other anti-PD-1 inhibitors ( Liu et al, 2020 ; Feng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven additional clinical cases described the development of PJP as a consequence of the use of immunosuppressants for the management of irAEs. Four patients were affected by melanoma [65,73,74], four by lung cancer [75], and one by Hodgkin's lymphoma [73]. In a retrospective study of 515 patients treated with ICIs for malignancy, 23 required treatment with high doses of corticosteroids secondary to the development of immune-mediated pneumonia, six (26%) of whom developed PJP (all in the absence of specific prophylaxis for PJP); in this study the presence of lymphopenia (lymphocytes < 755 cells/µL) was a predisposing factor for the development of PJP during steroid treatment [76].…”
Section: Icis and Opportunistic Infectionsmentioning
confidence: 99%